ANALISIS POLA PENERIMAAN GURU TERHADAP RAPOR ONLINE MENGGUNAKAN METODE UTAUT (STUDI KASUS PADA SMA NEGERI 8 SURABAYA) - Prasetyo Herfiyanto; Bambang Hariadi; Nunuk Wahyuningtyas (Jurnal Sistem Informasi Universitas Dinamika, 2018)
Rapor Online is one of the innovations made by Surabaya education authorities. The assesment method is intended to facilitate the task of teachers in the process of filling in report cards (rapor), as well parents so that they can access their child’s score on their report cards. But in practice, Rapor Online does not run well as expected by the city education authorities. The parents cannot access their children’s report cards quite often, with complaints such as slow access and others. Likewise for the teachers of SMA Negeri 8 Surabaya, the Rapor Online application actually adds to their burden. Often teachers have to proceed data input more than once, and also since the server is located only at the city education authorities, Rapor Online can be difficult to access simultaneously, especially when approaching the report card printing period. Therefore, researcher conducted a research related to the acceptance of teachers against Rapor Online. Researchers are using UTAUT as a reference, an acceptance model that has been formulated by Venkatesh, et. al.. Researchers are using all the teachers from SMA Negeri 8 Surabaya, both permanent and non-permanent teachers, as samples for this research. The results obtained in this study indicates the existence of three variabels that are quite influential to the pattern of acceptance of teachers in using the Rapor Online application. The three variables are Effort Expectancy, Social Influence and Behavioral Intention. Researchers convey if the process of data input in the Rapor Online can be made more quickly and easily, then the teacher will be glad using it, related to Behavioral Intention. As for the Social Influence variables, the school, fellow teachers and families must continue to support teachers so that they should keep follow the program that led by Surabaya education authorities.